International Organizations, Technical Assistance, and Domestic Investment Laws. Issue 1 (February 2023) - Berge, Tarald Gulseth; Fauchald, Ole Kristian
Abstract: Can supranational actors influence domestic policy? In this article, we study how international organizations have sought to shape the contents of domestic laws aimed at protecting foreign investment. Traditionally, the influence of international organizations on public policy has been assumed to run through loan conditionalities. We build on a recent strand of literature indicating that international organizations can also influence public policy through technical assistance. Empirically, we present a cross-sectional mapping of the protection that states offer foreign investors in domestic investment laws, and a mapping of the advisory activities of the three main organizations offering technical assistance on foreign investment laws: the United Nations Conference on Trade and Development, the Organization for Economic Co-operation and Development, and the World Bank. We find that there are significant variations in protection offered under domestic investment laws, and variation in international organizations' technical assistance over time and across organizations. To explore technical assistance as a causal mechanism for influence on public policy more closely in this field, we conduct a case study of the development of domestic investment legislation in Bosnia and Herzegovina.